Conservative Management of Delayed Submucosal Bleeding after Per-Oral Endoscopic Myotomy: A Case Report - Marrelli, Martina; Biasutto, Dario; Neri, Benedetto; Stigliano, Serena; Citterio, Nicolò; Pandolfi, Monica; Andrisani, Gianluca; Di Matteo, Francesco Maria (Acta medica Lituanica, 2024)
Per-Oral Endoscopic Myotomy (POEM) is recognized as the first-line therapy for achalasia, considering its high clinical efficacy and safety. Among the most important adverse events, bleeding or hematoma in the submucosal tunnel has incidence of approximately 1%.We describe the case of woman affected by type II achalasia, treated with POEM, who presented delayed bleeding with submucosal hematoma after starting anticoagulant therapy with subcutaneous low molecular weight heparin (LMWH).She presented with moderate-to-severe chest pain, stable vital signs and no evidence of arterial active bleeding. Therefore, urgent esophagogastroduodenoscopy was not performed, and the patient was treated conservatively with fasting, antibiotics, LMWH discontinuation and close medical supervision. After 10 days the condition was resolved, and the patients safely discharged.The present case report adds support to the safety and efficacy of conservative management of submucosal hematomas occurring after POEM.
Keywords: POEM; hematoma; submucosal bleeding; delayed bleeding